Pendampingan Literasi Berbasis Digital melalui Komunitas Belajar Baca-Cerdas di Desa Ciptodadi II Kecamatan Sukakarya - M.Syahrun Effendi; Sri Murti; Vella Sabrila Aisah; Riski Yongki Hidayat (LP4MK STKIP PGRI Lubuklinggau, 2024)
Based on the results of observations and interviews conducted with a village official, Mr. Feri Ardi Ragil Saputra, the Village Secretary, on July 5, 2024, in Ciptodadi II Village, it was found that the literacy level among the community, especially the youth group, is low. The initial evaluation results showed that literacy skills were categorized as